(NhRESTOMATIQ PO DIRIVIROWANIQ HOROM WYPUSK (B2s (NU^EBNOE POSOBIE(B,(NSME[ENNYE HORYs - (Ne(B.(NkRASOTINAs; (Nk(B.(Nr@MINAs; (N`(B.(NlEWITs ((NmOSKWAs (NmUZYKAs, 1969)
(NhRESTOMATIQ PO DIRIVOWANI@ HOROM SOOSTWETSTWII S U^EBNOJ PROGRAM(B.s
Keywords: (NsME[ANNYE HORYs